Ambient air pollution and out-of-hospital cardiac arrest. Israel nation wide assessment. (15th September 2021) - Kranc, Hannan; Novack, Victor; Shtein, Alexandra; Sonkin, Roman; Jaffe, Eli; Novack, Lena
Abstract: Introduction: Previous research suggested that an out-of-hospital cardiac arrest (OHCA) may be triggered by an exposure to ambient pollutants. Objective: We investigated the link between OHCA and a short-term exposure to particulate matter (PM) and other pollutants, within extreme climate conditions in Israel and high PM. Methods: In a case-crossover analysis, we analyzed all adult cases of OHCA in Israel during 2016–2017. The air-pollution and meteorology data were retrieved from the 132 monitoring stations. All associations at study were investigated using a lag-distributed regression and adjusted to temperature and humidity. Results: There were 12401 OHCA cases. Patients experiencing OHCA were likely to be exposed to elevated levels of pollutants, specifically, nitrogen dioxide (NO2 ) and particulate matter of size ≤2.5 μm (PM2.5 ) several hours prior to an event, although both at borderline significance, i.e. odds ratio (OR) = 1.20 (95%CI 0.96; 1.51) and OR = 1.15 (95%CI 0.84; 1.60), respectively. An exposure to NO2 was independently associated with OHCA among males (OR = 1.39, 95%CI 0.96; 2.01) and if occurred during the midweek (OR = 1.43, 95%CI 1.03; 1.97). The adverse effect of PM10 was more evident during a weekend (OR = 2.36, 95%CI 0.88; 6.28), as opposed to working days (OR = 0.81, 95%CI 0.45; 1.44). Analysis stratified by regions suggested a spatial variability in pollution associated with OHCA. Conclusions: Short-term exposure to high levels of pollution is adversely associated with OHCA independently of meteorological conditions. The magnitude of the effect is modified by patients' demography. Main finding: Short-term exposure to high levels of pollution is adversely associated with OHCA. This effect is independent of temperature and humidity. Highlights: We investigated an association between OHCA and a short-term exposure to pollutants, independet of climate conditions. Case-crossover methodology with lag-distributed technique were employed in the analysis. Patients experiencing OHCA were likely to be exposed to elevated levels of pollutants several hours prior to an event. An association with NO2 was more evident among males and during a midweek and with PM10 - during a weekend.